ADAPTIVE RECEPTION SYSTEM DESIGN WITH SPECTRUM SCAN FOR COGNITIVE RADIO - Ibarra Guerra, Yunior; Hernández Violat, Abel; Ramírez Zaldívar, Alexander Rogelio (Telemática, 2020)
In this paper, a digital reception system is proposed for a radio system with frequency agility. With frequency spectrum sensing for adaptive channel tuning the digital receiver avoid operate in high interference channels. With digital signal processing techniques like digital filters, decimators, NCO, and mixers the overall system is simulated and verified in Matlab. By Simulink model-based design flow the modeled blocks are synthesized in VHDL for final implementation in the Intel FPGA device. Finally, by system parameter measure is proved the used design method effectiveness. The methodology shows a way for software-defined radio design and implementation under a high spectral saturation environment keeping electromagnetic compatibility with other systems.